2021
DOI: 10.1007/s10803-021-05184-5
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes I Feel Grateful…”: Experiences of the Adolescent Siblings of Children with Autism Spectrum Disorder in Malaysia

Abstract: Sibling relationships remain understudied in typically developing adolescents who have siblings with autism spectrum disorder (ASD). This study explored the lived experiences and perceptions of adolescents who have a brother or a sister with a diagnosis of ASD using semi-structured interviews. Using thematic analysis, the participants reported having difficulties communicating with their siblings. Feeling a mixture of emotions was common when interacting with their siblings with ASD and emotional self-regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Instead, almost all typically developing kids, regardless of their position in the family, work with their parents to manage, care for, and safeguard their ASD siblings together (Hanvey et al, 2022). However, some research has indicated positive findings regarding sibling relationships, adopted coping, and typically developing child psychosocial adjustment while growing up with ASD individuals, where maturity, empathy, a sense of responsibility, and higher tolerance exist in this typically developing child because their parents have exposed them to the ASD issue that their siblings have experienced since childhood (Chu et al, 2021;Gorgy et al, 2017;Costa and Pereira, 2019;Mahbot & Alias, 2022). Most respondents in Singh and colleagues' study (2021) acknowledge that it can be challenging to manage their ASD siblings' behaviour and deal with difficulties, but they also concur that they grow to be more appreciative, independent, and grateful.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, almost all typically developing kids, regardless of their position in the family, work with their parents to manage, care for, and safeguard their ASD siblings together (Hanvey et al, 2022). However, some research has indicated positive findings regarding sibling relationships, adopted coping, and typically developing child psychosocial adjustment while growing up with ASD individuals, where maturity, empathy, a sense of responsibility, and higher tolerance exist in this typically developing child because their parents have exposed them to the ASD issue that their siblings have experienced since childhood (Chu et al, 2021;Gorgy et al, 2017;Costa and Pereira, 2019;Mahbot & Alias, 2022). Most respondents in Singh and colleagues' study (2021) acknowledge that it can be challenging to manage their ASD siblings' behaviour and deal with difficulties, but they also concur that they grow to be more appreciative, independent, and grateful.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, problem behaviours adversely affect caregivers financially, psychologically, and physically (15)(16)(17)(18)(19). Prior research has demonstrated that siblings of children with ASD often undergo emotional distress due to problem behaviours, affecting their upbringing and their relationship with their siblings with ASD (20,21).…”
Section: Introductionmentioning
confidence: 99%